SLC45A3-ELK4 is a Novel and Frequent ETS Fusion Transcript in Prostate Cancer - Rickman, David S. (2009)
Chromosomal rearrangements account for all erythroblast transformation specific (ETS) family member gene fusions that have been reported in prostate cancer and have clinical, diagnostic and prognostic implications. Androgen-regulated genes account for the majority of the 5’ genomic regulatory promoter elements fused with ETS genes. TMPRSS2-ERG, TMPRSS2-ETV1 and SLC45A3-ERG rearrangements account for roughly 90% of ETS fusion prostate cancer. ELK4, another ETS family member, is androgen-regulated, involved in promoting cell growth, and highly expressed in a subset of prostate cancer, yet the mechanism of ELK4 over-expression is unknown. In this study, we identified a novel ETS family fusion transcript, SLC45A3-ELK4, and found it to be expressed in both benign prostate tissue and prostate cancer. We found high levels of SLC45A3-ELK4 mRNA restricted to a subset of prostate cancer samples. SLC45A3-ELK4 transcript can be detected at high levels in urine samples from men at risk for prostate cancer. Characterization of the fusion mRNA revealed a major variant in which SLC45A3 exon 1 is fused to ELK4 exon 2. Based on quantitative PCR analyses of DNA, unlike other ETS fusions described in prostate cancer, the expression of SLC45A3-ELK4 mRNA is not exclusive to cases harbouring a chromosomal rearrangement. Treatment of LNCaP cancer cells with a synthetic androgen (R1881) revealed that SLC45A3-ELK4, and not endogenous ELK4, mRNA expression is androgen-regulated. Altogether, our findings show that SLC45A3-ELK4 mRNA expression is heterogeneous, highly induced in a subset of prostate cancers, androgen-regulated, and most commonly occurs through a mechanism other than chromosomal rearrangement (e.g., trans-splicing).